Optimal capacitor allocation in distribution systems using genetic algorithm - Singh S.P.; Kistanna C.; Rao A.R. (My University, 2025)
The Genetic Algorithm (GA) has been used to solve the capacitor placement problem in a radial distribution system. This problem considers practical operating constraints of capacitors, capacity of the feeder and the upper and lower bound constraints on voltage at different load levels to minimize the investment cost of capacitors and system energy loss. A sensitivity analysis method is used to select the candidate installation locations of the capacitors to reduce the search space of this problem a priori. A simple iterative method is used to compute the power flow. The results obtained for 69-branch system are compared with the solutions obtained by Tabu Search (TS) and Hybrid Approach techniques. It is demonstrated that the proposed Genetic Algorithm method offers the global optimal solution with greater saving. © 2008 CRL Publishing Ltd.